(untitled) (Al-Qamar, 2025)
The preservation and documentation of the teachings of the Prophet Muhammad (peace be upon him) have remained a central scholarly pursuit across the centuries. Leading this endeavor were not only the eminent scholars of Hadith but also experts from diverse fields who contributed significantly within their expertise. Among them was a group of revered Sufis who diligently acquired Hadith knowledge under the guidance of their teachers and also got permission to narrate authentic, directly transmitted (marfu‘ muttasil) Hadiths from them. These Sufis integrated such narrations into their teachings, sermons, and written works. A significant number of these Sufis are referenced in major Hadith compilations, with their narrations documented through their chains of authority by prominent Hadith scholars. Foundational Hadith sources, including the Sahih Sitta, Musnad al-Darimi, Sunan al-Darimi, Musannaf Ibn Abi Shaybah, Musannaf Abdal-Razzaq, Musnad Ahmad, Musnad Ishaq ibn Rahawayh, and Mustadrak Hakim, among others, incorporate narrations from Sufis, as documented by leading Hadith authorities. Subsequent Hadith scholars further affirmed the reliability of these transmission chains. This study will concisely examine the biographies of selected Sufi scholars from the first to the tenth Hijri century and evaluate the perspectives of Hadith scholars on their trustworthiness, affirming the authenticity of their narrations. Furthermore, the refinement and validation of these narrated Hadiths, along with their chains of transmission, will be thoroughly executed.